Peran Keterlibatan Orangtua dalam Mengembangkan Sosial-Emosional Anak Pra-Sekolah - Verlianti M Wijaya; Luluk Asmawati; Tri Sayekti (Darul Yasin Al Sys, 2026)
The social and emotional development of early childhood is an important aspect in the formation of character and the ability to interact at subsequent stages of development. However, not all children receive optimal support from the family environment, especially in the form of parental involvement in the process of child care and education. This study aims to describe the role of parental involvement in developing the social and emotional abilities of children aged 5–6 years at TK Putra II Serang, Banten. This study employed a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects included children aged 5–6 years in Group B2, parents, and teachers at TK Putra II Serang. Data analysis was carried out through the stages of data reduction, data display, and conclusion drawing based on the Miles and Huberman model. The results showed that parental involvement played an important role in children’s social and emotional development through the provision of emotional support, positive behavioral role modeling, and active participation in children’s daily activities. Children who received attention and assistance from their parents tended to have better self-confidence, better socialization skills, and more stable emotional regulation abilities. These findings emphasize that the active role of parents as educators, mentors, and role models influences the optimization of children’s social and emotional development. The implications of this study indicate the importance of increasing parental awareness and sustained involvement in supporting children’s development from an early age in order to achieve optimal social and emotional development.